2008
DOI: 10.1007/s10903-008-9179-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Acculturation and Alcohol Use among Latina/o Adolescents: A Multi-Ethnic Comparison

Abstract: This is the first study to examine the relationship between acculturation and alcohol use by gender and ethnicity using a nationally representative sample of Hispanic and non-Hispanic white adolescents. Specifically, we use data from the National Longitudinal Study of Adolescent Health (Add Health) to explore alcohol use and binge drinking for a sample that includes 6792 non-Hispanic whites, 910 Mexican Americans, 290 Cuban Americans, and 336 Puerto Ricans. Bivariate results reveal significant gender differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
62
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 42 publications
5
62
2
Order By: Relevance
“…After adjusting for sociodemographic differences, third generation reported less lifetime alcohol use and fewer friends using alcohol, but higher intent to use alcohol and marijuana in the next 12 months, than both first and second generation. These findings are contradictory to previous reports that first generation Latina/o youth are less likely to engage in alcohol use compared with more acculturated youth [1,20,32]. Overall, healthy behaviors did not change with greater acculturation among Latinas, which also contradicts previous findings [18].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…After adjusting for sociodemographic differences, third generation reported less lifetime alcohol use and fewer friends using alcohol, but higher intent to use alcohol and marijuana in the next 12 months, than both first and second generation. These findings are contradictory to previous reports that first generation Latina/o youth are less likely to engage in alcohol use compared with more acculturated youth [1,20,32]. Overall, healthy behaviors did not change with greater acculturation among Latinas, which also contradicts previous findings [18].…”
Section: Discussioncontrasting
confidence: 99%
“…Health disparities in Latino/a(s) have become of increasing interest because this population has grown significantly in recent decades, emerging as the largest minority group in the United States [1]. Latino/a(s) are vulnerable to poor health outcomes for a variety of reasons, including lack of health care services [2,3], environmental exposures [4], and potentially detrimental health-related behaviors [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of study participants had lived in the United States for a large proportion of their lives (years in the United States, M = 16.20, SD = 3.92, range: 1-19 years) and were similarly oriented to Mexican and American cultures (ARSMA-II Mexican, M = 3.77, SD = 0.59; and Anglo, M = 3.79, SD = 0.40). Given that the baseline heavy drinking episode rate was similar among Mexican American men and women, the current fi ndings support previous studies that found an association between U.S. cultural orientation and drinking among women but not men (Wahl and Eitle, 2010). Additionally, it is possible that cultural orientation alone may not adequately represent ethnic identity.…”
Section: Discussionsupporting
confidence: 72%
“…High levels of familism, or strength of family relationships, is a traditionally Hispanic value, and high parental respect is a traditionally Asian value (Kaplan et al, 2001;Unger et al, 2002). Hispanic adolescents with higher familism have decreased risk for cigarette initiation (Kaplan et al, 2001) and heavy drinking (Wahl and Eitle, 2010), and Asians may be less likely to disobey their parents' rules related to substance use .…”
mentioning
confidence: 99%